Spirituality in Nursing Theory and Practice: Dilemmas for Christian Bioethics - Salladay, Susan Anthony (Christian bioethics, 1997)
Moral strangerhood is due in part to competing worldviews. The profession of nursing is experiencing a paradigm shift which creates ethical dilemmas for both Christian nurses and Christian patients. Nursing's new focus on spirituality and spiritual care presents itself as broadly defining a desired state or patient outcome — spiritual integrity — supposed to be applicable to all patients of all faiths. Analysis of nursing's definition of spirituality reveals assumptions and values consistent with an Eastern/New Age worldview which may cause hostility towards Christian patients stereotyped as dogmatic or noncompliant.